ANALISIS PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILIY (CSR) TERHADAP KINERJA KEUANGAN (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2014) - Indrawati Mara Kesuma (Universitas Indo Global Mandiri)
This research try to see the relationship between the large of company social responbility with the financial performance. The goal of this research was to know the effect of environment theme energy, employment, product and consumer theme community theme effected in partial and simultant way to ROA. The population of this research was 150 manufactures company which listed in Indonesia stock exchange in 2012 until 2014 and the sample of this research was 45 companies which fulfill the research criteria. From the research can be conluded that 1) enviroment energy theme and employment theme not effected and significant to ROA, product theme and consumer theme efected and not significant to ROA. While community theme not effected but significant to ROA. 2) Environent and energy, employment, product and consumer, community in together effected and significant to ROA.Key words : CSR, finansial performance, ROA